Productive Zakat and Poverty Alleviation Through (Cibest Model Approach) at Baznas, Kendari City, Southeast Sulawesi Province - Rahmah Rafifah Abu; Abdul Wahab; Idris Parakkasi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Poverty remains a major challenge to economic development in Indonesia, including in Kendari City, Southeast Sulawesi Province. One instrument believed to provide a solution to this problem is zakat, particularly productive zakat. This study aims to analyze the role of productive zakat in poverty alleviation through the CIBEST Model approach at the National Aznas (BAZNAS) in Kendari City, Southeast Sulawesi Province. The CIBEST Model offers a comprehensive approach that measures poverty not only from a material perspective but also from a spiritual perspective.The results of the study indicate that the poverty level and welfare of mustahiq (recipients) in BAZNAS Kendari City experienced significant changes after the implementation of productive zakat. Based on the CIBEST Model approach, there was an increase in material and spiritual welfare among beneficiaries, with the welfare category of Quadrant I increasing from 5 to 8 households. Quadrant II, the material poverty category, decreased from 5 to 2 households. Meanwhile, no households fell into the spiritual and absolute poverty categories after receiving productive zakat. However, the implementation of productive zakat has not been fully effective, with 2 out of 10 informants still classified as poor due to business location and health conditions. Nevertheless, their spiritual aspects showed positive development. BAZNAS needs to strengthen training, mentoring, and business supervision, although limited human resources remain a barrier.